2012
DOI: 10.1038/ejhg.2012.90
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mutations in XPD(ERCC2) on pregnancy and prenatal development in mothers of patients with trichothiodystrophy or xeroderma pigmentosum

Abstract: The XPD(ERCC2) gene encodes a DNA helicase involved in DNA repair and transcription. Patients with mutations in XPD may have different autosomal recessive phenotypes including trichothiodystrophy (TTD) or xeroderma pigmentosum (XP). TTD patients have sulfur-deficient, brittle hair, short stature and developmental delay. In contrast, XP patients have freckle-like pigmentation and a greatly increased risk of sun-induced skin cancers. Mothers of TTD patients have been reported to have a high frequency of pregnanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 27 publications
3
14
0
Order By: Relevance
“…Recent molecular epidemiological studies on pregnancy and neonatal abnormalities in the mothers of patients with XPD mutations showed that 94% of TTD pregnancies (16 of 17) have preterm delivery, pre-eclampsia, hemolysis, elevated liver enzymes and low platelets syndrome, prematurity, and low birth weight. In contrast, none of 17 XP pregnancies had these complications (35,36). It is worthwhile considering that the human placenta, whose function is to facilitate nutrient exchanges between the fetus and the mother, contains abundant ECM components and well-preserved endogenous growth factors.…”
Section: Discussionmentioning
confidence: 99%
“…Recent molecular epidemiological studies on pregnancy and neonatal abnormalities in the mothers of patients with XPD mutations showed that 94% of TTD pregnancies (16 of 17) have preterm delivery, pre-eclampsia, hemolysis, elevated liver enzymes and low platelets syndrome, prematurity, and low birth weight. In contrast, none of 17 XP pregnancies had these complications (35,36). It is worthwhile considering that the human placenta, whose function is to facilitate nutrient exchanges between the fetus and the mother, contains abundant ECM components and well-preserved endogenous growth factors.…”
Section: Discussionmentioning
confidence: 99%
“…ERCC2 is a component of transcription factor IIH (TFIIH), essential for basal transcription and nucleotide excision repair, which is disturbed in TTD patients. Other subunits of TFIIH are ERCC3 (mutations lead to photosensitive TTD2 and to XP group B) and GTF2H5 (mutations lead to photosensitive TTD3), but ERCC2 (XPD) is most frequently mutated . Alternations in the ERCC2 subunit may lead to multiple phenotypes other than TTD: xeroderma pigmentosum (XP), Cockayne syndrome (CS), cerebro‐oculo‐facio‐skeletal (COFS) syndrome and a complex overlap phenotype .…”
Section: Discussionmentioning
confidence: 99%
“…Newborns frequently present with a collodion membrane, followed by ichthyosis of the skin and nail deformities like brittleness, koilonychia and onychoschizia. Additional important features of TTD include pregnancy and birth complications, growth restriction, neurological impairment, gonadal dysgenesis, haematological and ophthalmological abnormalities and recurrent life‐threatening infections . Moreover, TTD is associated with an up to 20‐fold increased risk of death before the age of 10 years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TTD-1 is characterised by brittle sulphur-deficient hair, photosensitivity, developmental abnormalities and reduced life span [109]. Pregnancies with a TTDaffected foetus were retrospectively shown to have had abnormally high rates of pregnancy complications (placentation abnormalities, HELLP syndrome, preeclampsia), abnormal levels of routine biochemical markers, a significant percentage (70 %) of low birth weight infants (half of which were below the 10th percentile for gestational age) and were significantly more likely to have been delivered prematurely by emergency caesarean section because of fetal distress [110]. TTD-1 is caused by mutations in the gene XPD (ERCC2), coding for a DNA helicase unwinding the DNA at the site of damage and allowing unimpeded access of the cellular machinery for nucleotide excision repair (NER) [109].…”
Section: Role Of the Individual Repair Capacity In The Constitution Omentioning
confidence: 99%